2022
DOI: 10.1088/1748-605x/ac9f90
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically crosslinked hydrogel based on tyramine modified gelatin and sialylated chitosan

Abstract: The enzymatically crosslinked hydrogel could replicate the cellular microenvironment for biomedical applications. In the present study, to improve the cytocompatibility of chitosan (CS), sialic acid (SA) was introduced to CS to synthesize sialylated CS (CS-SA), and the tyramine (TA) was grafted to gelatin (G) to obtain TA modified gelatin (G-TA). The successful synthesis of CS-SA and G-TA was confirmed using 1H NMR and UV-Vis absorption spectra. The interpenetrating polymer networks (IPN) G-TA/CS-SA (GC) hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Next, the rheological properties of hydrogels were further investigated, and the storage moduli (G') and loss moduli (G'') of hydrogels were tested in terms of temperature and frequency (Figures 3H and 3I). The results show that G' of all obtained hydrogels is greater than G'', exhibiting the typical viscous flow characteristics of hydrogel [39,59,60]. There was a slight increase in both G' and G'' with the increase of temperature from -4 °C to 60 °C.…”
Section: Physiochemical Properties Of Bioactive Composite Hydrogelsmentioning
confidence: 78%
“…Next, the rheological properties of hydrogels were further investigated, and the storage moduli (G') and loss moduli (G'') of hydrogels were tested in terms of temperature and frequency (Figures 3H and 3I). The results show that G' of all obtained hydrogels is greater than G'', exhibiting the typical viscous flow characteristics of hydrogel [39,59,60]. There was a slight increase in both G' and G'' with the increase of temperature from -4 °C to 60 °C.…”
Section: Physiochemical Properties Of Bioactive Composite Hydrogelsmentioning
confidence: 78%
“…These results indicate that the hydrogels possessed good biocompatibility. In our previous research [25,46,47], SF and chitosan were used to fabricate hydrogels dressings for wound healing application by compositing with other polymers or loading antibiotic drugs. In this work, the hydrogel dressings could be designed and obtained based on the host-guest interactions and hydrogen-bonding assembly from SF and chitosan.…”
Section: In Vitro Biocompatibility Of Qca Hydrogelsmentioning
confidence: 99%
“…According to the report, different EDCI/NHS and buffer systems were considered [35][36][37][38][39]. It was found that when the ratio of NHS to EDCI exceeded one, there was almost no unreacted adenine and thymine.…”
Section: Preparation Of Cmc-at Nanofiber Hydrogel Adhesivementioning
confidence: 99%